The Comprehensive Archive of Substellar and Planetary Accretion Rates - S. K. Betti; K. B. Follette; K. Ward-Duong; A. E. Peck; Y. Aoyama; J. Bary; B. Dacus; S. Edwards; G.-D. Marleau; K. Mohamed; J. Palmo; C. Plunkett; et al. (The Astronomical Journal, 2023)
Accretion rates ( $\dot{M}$ ) of young stars show a strong correlation with object mass ( M ); however, extension of the $\dot{M}--M$ relation into the substellar regime is less certain. Here, we present the Comprehensive Archive of Substellar and Planetary Accretion Rates (CASPAR), the largest compilation to date of substellar accretion diagnostics. CASPAR includes: 658 stars, 130 brown dwarfs, and 10 bound planetary mass companions. In this work, we investigate the contribution of methodological systematics to scatter in the $\dot{M}--M$ relation and compare brown dwarfs to stars. In our analysis, we rederive all quantities using self-consistent models, distances, and empirical line flux to accretion luminosity scaling relations to reduce methodological systematics. This treatment decreases the original 1 σ scatter in the $log\dot{M}--logM$ relation by ∼17%, suggesting that it makes only a small contribution to the dispersion. The CASPAR rederived values are best fit by $\dot{M}\propto {M}^{2.02± 0.06}$ from 10 M _J to 2 M _⊙ , confirming previous results. However, we argue that the brown-dwarf and stellar populations are better described separately and by accounting for both mass and age. Therefore, we derive separate age-dependent $\dot{M}--M$ relations for these regions and find a steepening in the brown-dwarf $\dot{M}--M$ slope with age. Within this mass regime, the scatter decreases from 1.36 dex to 0.94 dex, a change of ∼44%. This result highlights the significant role that evolution plays in the overall spread of accretion rates, and suggests that brown dwarfs evolve faster than stars, potentially as a result of different accretion mechanisms.